2016
DOI: 10.1002/2016gl069692
|View full text |Cite
|
Sign up to set email alerts
|

Stable reconnection at the dusk flank magnetopause

Abstract: The dusk flank magnetopause was surveyed with instruments on board the Magnetospheric Multiscale (MMS) spacecraft on 28 August 2015 between 13:55 UT and 14:15 UT during a period of persistent southward interplanetary magnetic field (IMF) with varying dawn‐dusk component. Plasma measurements (500 eV electrons, > 2 keV ions) revealed the existence of at least one active reconnection region that persisted throughout the interval. The reconnection region convected equatorward despite the poleward and tailward magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…If the magnetosheath flow is between 1 and 2 times the Alfvén speed, then reconnection X‐lines may convect with the magnetosheath flow such that the flow is Alfvénic in the deHoffmann‐Teller frame [see, e.g., Gosling et al , ], but reconnection is not possible if the magnetosheath flow is faster. Observations at the high‐latitude magnetopause [ Fuselier et al , ; Lavraud et al , ] and on the flanks [ Gomez et al , ] of stable reconnection X‐lines in magnetosheath flow conditions that were marginally sub‐Alfvénic appear to support this suggestion. However, there is also evidence of motion of the X‐line in the presence of magnetosheath flow [ Wilder et al , ] and a suggestion that an isolated reconnection X‐line may convect with the flow even if the flow is sub‐Alfvénic [ Doss et al , ].…”
Section: Magnetosheath Flow Velocitiesmentioning
confidence: 91%
“…If the magnetosheath flow is between 1 and 2 times the Alfvén speed, then reconnection X‐lines may convect with the magnetosheath flow such that the flow is Alfvénic in the deHoffmann‐Teller frame [see, e.g., Gosling et al , ], but reconnection is not possible if the magnetosheath flow is faster. Observations at the high‐latitude magnetopause [ Fuselier et al , ; Lavraud et al , ] and on the flanks [ Gomez et al , ] of stable reconnection X‐lines in magnetosheath flow conditions that were marginally sub‐Alfvénic appear to support this suggestion. However, there is also evidence of motion of the X‐line in the presence of magnetosheath flow [ Wilder et al , ] and a suggestion that an isolated reconnection X‐line may convect with the flow even if the flow is sub‐Alfvénic [ Doss et al , ].…”
Section: Magnetosheath Flow Velocitiesmentioning
confidence: 91%
“…Bursts of ≥500 eV electrons in the MSBL that switch from being primarily antiparallel streaming (relative to the magnetic field) to parallel streaming or vice versa provide independent evidence of the proximity of an X line to the spacecraft. Both of these types of observations indicate connection to a nearby reconnection site that is moving relatively northward or southward over the spacecraft [see Gomez et al ., ] or passing through the reconnection site in or near the diffusion region [see Wilder et al ., ]. Finally, oppositely directed ion jets or oppositely directed electron bursts observed on two different spacecraft provide a third, independent way to demonstrate that the spacecraft were “straddling” a reconnection X line.…”
Section: Survey Methodology and Data Setsmentioning
confidence: 99%
“…Shown in Figure 1, C1 is northward and duskward of C3 and is north of the predicted component reconnection line. If the flow reversals observed by C1 were a consequence of the reconnection line responding to changes in the IMF, a mechanism suggested by Gomez et al [2016] and Trattner et al [2016], then C1 should have observed northward ion jets primarily. For C1, then, the motion of the reconnection site inferred from the ion flow reversals could be due to magnetic islands convecting away from the primary reconnection site, or possibly from observations of a second, active reconnection site at higher latitudes.…”
Section: Shown Inmentioning
confidence: 96%
See 1 more Smart Citation
“…Combining simple mathematical expressions to approximate the global picture of conditions adjacent to a planetary magnetopause has been extensively used to investigate the interaction between the solar wind and Earth's magnetosphere (Cooling et al, ; Crooker, ; Dunlop et al, ; Fuselier et al, , , ; Gomez et al, ; Kobel & Flückiger, ; Komar et al, ; Luhmann et al, ; Petrinec & Russell, ; Petrinec et al, , , , ; Souza et al, ; Trattner et al, , , , , , ; Vines et al, ; Wilder et al, ). This considerable terrestrial modeling heritage formed the foundation of recent, similar investigations of the solar wind interaction with Saturn, Uranus, and Neptune (Masters, , , ), and these giant planet models are precursors of the present Jupiter model.…”
Section: Modeling Conditions At Jupiter's Magnetopause Under Steady Smentioning
confidence: 99%